O'Brien's Granuloma in a 50-year-old Chinese male - Huang Changzheng; Loai Sami (Our Dermatology Online, 2015)
O'Brien's actinic granuloma is clinically characterized by grouped red papules that may coalesce into annular plaques on sun damaged skin such as the head and neck, chest, and arms. There is no gender predilection, and patients tend to be middle-aged or older giving the association with significant actinic damage. We presented a 50-year-old male with multiple annular lesions on the neck of four years duration, associated with prolonged sun exposure. A biopsy confirmed the clinical suspicion of O'Brien's granuloma and excluded other possibilities.